The Effect of Dhikr Meditation on Blood Pressure Changes in Elderly with Hypertension in Gowa Regency - Islamiyah Islamiyah (HM Publisher, 2020)
Hypertension increases blood pressure that results in the supply of oxygen and nutrients being blocked by the blood reaching the body's tissues that need it. This study aims to determine the effect of dhikr meditation on changes in blood pressure in the elderly with hypertension in Gowa Regency. This research was conducted in Gowa Regency, South Sulawesi, Indonesia. This research method is experimental research with pre and post-test design. The number of samples is 15 people using the purposive sampling technique. Data collected using questionnaires and observation sheets were analyzed by Paired t-test. The results showed an effect of dhikr meditation on changes in blood pressure in the elderly with hypertension. So that it can be concluded, there is a significant effect between dhikr meditation and changes in blood pressure in the elderly with hypertension in Gowa Regency.